2011
DOI: 10.1080/01635581.2011.551987
|View full text |Cite
|
Sign up to set email alerts
|

Inflammation-Related Signaling Pathways Implicating TGFβ are Revealed in the Expression Profiling of MCF7 Cell Treated with Fermented Soybean, Chungkookjang

Abstract: Chungkookjang is a Korean fermented soybean containing microorganisms, proteinase, and diverse bioactive compounds, including a high concentration of isoflavones and peptides. Growth of breast cancer MCF7 cells decreased dependent on the concentration of fermented soybean extracts. The effect of fermented soybean on cellular gene expression was determined in a systematic manner comprehensively. DNA microarray analysis was performed using 25,804 probes. Ninety one genes whose expression levels were significantl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
10
0
3

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
4

Relationship

3
7

Authors

Journals

citations
Cited by 32 publications
(14 citation statements)
references
References 41 publications
1
10
0
3
Order By: Relevance
“…Soybean hydrolysates have yielded several bioactive peptides with anti-inflammatory effects on macrophage cell lines, with preparations from germinated beans eliciting the stronger responses [35]. Chungkookjang, a fermented soybean product from Korea, is rich in bioactive peptides and shows anti-inflammatory effects in breast cancer cells by downregulation of cytokine/chemokines expression and activation of transforming growth factor (TGF)-beta signaling [36]. One of the soybean-derived peptides, lunasin, appears to exert widespread anti-inflammatory effects including suppression of NF- κ B activity, reduced cytokine expression, and reduction in cyclooxygenase-2 (COX-2) levels in addition to its antioxidant and anticarcinogenic properties [37, 38].…”
Section: Bioactive Peptides On Inflammationmentioning
confidence: 99%
“…Soybean hydrolysates have yielded several bioactive peptides with anti-inflammatory effects on macrophage cell lines, with preparations from germinated beans eliciting the stronger responses [35]. Chungkookjang, a fermented soybean product from Korea, is rich in bioactive peptides and shows anti-inflammatory effects in breast cancer cells by downregulation of cytokine/chemokines expression and activation of transforming growth factor (TGF)-beta signaling [36]. One of the soybean-derived peptides, lunasin, appears to exert widespread anti-inflammatory effects including suppression of NF- κ B activity, reduced cytokine expression, and reduction in cyclooxygenase-2 (COX-2) levels in addition to its antioxidant and anticarcinogenic properties [37, 38].…”
Section: Bioactive Peptides On Inflammationmentioning
confidence: 99%
“…16 Soybeans soaked for 18 h were autoclaved at 120°C for 30 min. Bacillus licheniformis B1 (1% in culture) was added onto 1 kg of autoclaved soybeans.…”
Section: Chu Preparationmentioning
confidence: 99%
“…Few studies have been carried out the anti-inflammatory activity of peptides derived from Korean fermented soybean products (Lee et al, 2014). Hwang et al (2011) demonstrated that a bioactive peptide from chungkookjang exhibited anti-inflammatory effects in breast cancer cells by activation of transforming growth factor (TGF)-beta signaling and down-regulation of cytokine/chemokine expression. An inhibitory effect on the NO production in LPS-stimulated cells was observed in fractions of nitrogenous compounds separated by molecular weight level from water extracts of doenjang (WED) (Lee et al, 2014).…”
Section: Introductionmentioning
confidence: 99%